Konsep Keraguan Dalam Islam - Oktaviyani, Aisyah; Rifai, Ahmad; Alif, Muhammad; Saputra, Edriagus (Institut Agama Islam Sumatera Barat Pariaman, 2024)
This situation occurs based on the fact that a person cannot be in two different places at the same time. Conflict and doubt is an attitude that is often experienced by every human being, although the form and quality of conflict and doubt is different for each individual. This research uses qualitative methods in the form of library research. The results of this study can be concluded, that as a Muslim, every action or something that is to be decided, should be done after maximum consideration, so that there is no doubt in carrying it out. Even in believing in Allah and the Pillars of Faith, every Muslim should not have doubts about what he believes, so that he has complete and perfect faith in Allah and all that must be believed. So in addressing the steps to overcome the attitude of doubt, namely strengthening skills and abilities, discussion / asking for other people's opinions, self-confidence, planning the actions to be taken and being ready to bear the risks of the actions taken.